The Making of Smart Campus: A Review and Conceptual Framework - Ken Polin; Tan Yigitcanlar; Mark Limb; Tracy Washington (Buildings, 2023)
Smart campus is an emerging concept enabled by digital transformation opportunities in higher education. Smart campuses are often perceived as miniature replicas of smart cities and serve as living labs for smart technology research, development, and adoption, along with their traditional teaching, learning and research functions. There is currently a limited understanding of how the smart campus is conceptualized and practiced. This paper addresses this gap by using a systematic literature review following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) approach. The study uses four major domains of the smart campus, i.e., society, economy, environment, and governance, to classify existing research. These domains are each aligned to the central smart campus concepts of digital technology and big data. The analysis found little evidence of a comprehensive real-world application of the smart campus towards addressing all four domains. This highlights the infancy of the current conceptualization and practice. The findings contribute to the development of a new conceptual foundation and research directions for the smart campus notion and informs its practice through a conceptual framework. The findings reported in this paper offer a firm basis for comprehensive smart campus conceptualization, and also provide directions for future research and development of smart campuses.